Scholastic pocket thesaurus - Bollard, John K. (New York : Scholastic, 2002)
Provides a brief definition and lists of synonyms for common English words, with a cross-referencing index arranged throughout the book alphabetically.
Keywords: Language arts -- Non-fiction; Reference -- Non-fiction